Effectiveness of Immersive VR for Reflective Learning in Architectural Technology and Construction Management Education - Jørsfeldt, Liliyana Makarova; Haahr, Meinhardt Thorlund (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This study investigates the practice of reflective learning in construction management education by exploring the integration of immersive virtual reality (VR) technologies. Traditional educational approaches often struggle to provide students with immersive and practical experiences that replicate real-world construction scenarios. VR offers an innovative solution by enabling experiential learning in a risk-free environment, supporting the development of critical skills such as decision-making, safety management, and project execution. The research employs a Design-Based Research methodology to design and evaluate interventions that integrate VR into educational frameworks. These interventions are guided by the Reflective Practice-Based Learning (RPL) principle: “Teaching and learning activities are organized as exploration.” The study uses qualitative analysis to examine how VR can enhance students’ reflection, deepen understanding, and support knowledge transfer and skill development in building design. The findings provide insights into how VR can facilitate meaningful engagement with complex building designs and contribute to the near and far transfer in learning. The immersive VR in education demonstrates significant potential for transforming traditional educational methods. The study’s practical implications lie in providing new educational designs that combine technological tools with reflective, practice-oriented learning approaches.